Left ventricular to right atrial shunt resulting from infective endocarditis. - Ellis, C J (1975)
A unique case is described in which infective endocarditis of the aortic valve led to intractable heart failure and necropsy examination showed that the patient had developed a communication between the left ventricle and right atrium.